New Insights into the Genetic Diversity of Clostridium botulinum Group III through Extensive Genome Exploration - Woudstra, Cédric; Le Maréchal, Caroline; Souillard, Rozenn; Bayon-Auboyer, Marie-Hélène; Mermoud, Isabelle; Desoutter, Denise; Fach, Patrick (Frontiers in Microbiology, 2016)
Animal botulism is caused by group III Clostridium botulinum strains producing type C and D toxins, or their chimeric forms C/D and D/C. Animal botulism is considered an emerging disease in Europe, notably in poultry production. Before our study, 14 genomes from different countries were available in the public database, but none were from France. In order to investigate the genetic relationship of French strains with different geographical areas and find new potential typing targets, 17 strains of C. botulinum group III were sequenced (16 from France and one from New Caledonia). Fourteen were type C/D strains isolated from chickens, ducks, guinea fowl and turkeys and three were type D/C strains isolated from cattle. The New Caledonian strain was a type D/C strain. Whole genome sequence analysis showed the French strains to be closely related to European strains from C. botulinum group III lineages Ia and Ib. The investigation of CRISPR sequences as genetic targets for differentiating strains in group III proved to be irrelevant for type C/D due to a deficient CRISPR/Cas mechanism, but not for type D/C. Conversely, the extrachromosomal elements of type C/D strains could be used to generate a genetic ID card. The highest level of discrimination was achieved with SNP core phylogeny, which allowed differentiation up to strain level and provide the most relevant information for genetic epidemiology studies and discrimination.